Comparison of hot corrosion behaviour of FGM and usual TBCs. (3rd June 2017) - Rahnavard, M.; Ostad Ahmad Ghorabi, M. J.; Rafiee, H.
Abstract : In the present paper, hot corrosion behaviour of functionally graded material (FGM) and usual ceria-yttria stabilised zirconia (CYSZ) TBCs, prepared by atmospheric plasma spraying method was evaluated. In addition, coating microstructures were investigated using scanning electron microscope; EDS and X-ray diffraction techniques before and after hot corrosion test. The results showed, due to different corrosion mechanisms, the life of FGM TBC was higher than the usual one. The degradation mechanism of usual TBC was formation of TGO at the bond coat/CYSZ layer interface resulted in delamination, while in FGM coating was the stress induced by phase transformation volume increment occurred in the coating and the thermal stress accompanied by thermal expansion mismatch.